Effects of functional limitations and activities of daily living on the mortality of the older people: A cohort study in China - Gao, Yumeng; Du, Liang; Cai, Jianping; Hu, Tingfa (Frontiers in Public Health, 2023)
Prevalence of functional limitations (FLs) and disabled activities of daily living (ADL) cause heavy burdens to the health of the older people. Stratified by gender, this study aimed to explore the effects of FL and ADL on the mortality of the older people in China, and the mechanism was then discussed. We used survey data of a prospective 10-year cohort (2008-2018), from the China Longitudinal Healthy Longevity Survey (CLHLS). The primary outcome was all-cause mortality, and Independent variables included FL, basic ADL (BADL), and instrumental ADL (IADL). Covariates involved socio-demographic characteristics, health-related behaviors, and health status of the participants in the CLHLS project. There were 967(19.20%) male and 2235(32.36%) female older people performed functional limitations, and their survival time was 60.98 (SE=0.66) and 55.19 (SE=0.55) months, respectively. Old adults with FL had significantly poorer survival than the ones without (Log-rank test, P<0.001). Weibull regression suggested that FL (P<0.001), abnormal BADL (P<0.001) and IADL (P<0.001) were negatively associated with the survival of the older people. Further analysis showed that BADL and IADL performed significantly mediating roles in the relation of FL and survival time in old adults; additionally, for female older people, BADL also exhibited a significant moderating role in the effect of FL on survival. Prevalence of FL was serious among the older people in China, especially for the women. Disabilities of BADL and IADL and FL were negatively associated with the survival time of the older people in China. Regarding the effect of FL on survival, BADL and IADL performed significantly mediating roles, and the moderating role of BADL existed only for the female. These suggested evidence to implement strategies to maintain health in the older people.